2018
DOI: 10.1002/jcb.27276
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of long noncoding RNA MEG3 expression in the survival of patients with cancer: A meta‐analysis

Abstract: Long noncoding RNAs (lncRNAs) play an important role in carcinogenesis and cancer progression. lncRNA maternally expressed gene 3 (MEG3) is a tumor suppressor that is downregulated in several cancers. However, its prognostic value in human malignancies remains controversial. We have therefore undertaken a meta-analysis to explore the relationship between cancer survival and the expression of lncRNA MEG3. A systematic literature search identified 13 potentially eligible investigations comprising 1733 patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…It is, however, there is no difference between the low expression of MEG3 and worse outcome (or high risk of death probabilities) OR high expression of MEG3 and good prognosis (or subjects have a low risk of death probabilities). [2][3][4] In line with our paper, Wang et al 4 reported a similar finding about the prognostic value of MEG3. In particular, they found that decreased MEG3 expression was predicted poorer survival/metastasis outcomes in patients with multiple cancers with HR of 0.41 (95% confidence interval [CI]: 0.24-0.70, P < 0.001).Second, we need to emphasize that, the cited reference 5 of the letter by BLINDED, reported the similar data, compared to our paper.…”
supporting
confidence: 87%
“…It is, however, there is no difference between the low expression of MEG3 and worse outcome (or high risk of death probabilities) OR high expression of MEG3 and good prognosis (or subjects have a low risk of death probabilities). [2][3][4] In line with our paper, Wang et al 4 reported a similar finding about the prognostic value of MEG3. In particular, they found that decreased MEG3 expression was predicted poorer survival/metastasis outcomes in patients with multiple cancers with HR of 0.41 (95% confidence interval [CI]: 0.24-0.70, P < 0.001).Second, we need to emphasize that, the cited reference 5 of the letter by BLINDED, reported the similar data, compared to our paper.…”
supporting
confidence: 87%
“…It is down-regulated in several malignancies such as prostate cancer [120], oral cell carcinoma [121] and BC [122]. In BC patients, MEG3 was directly associated with the overall-survival of patients thus highlighting its high prognostic value in BC [123]. It has been reported to act as a tumor suppressor lncRNA through acting as a sponge to several miRNAs such as miR-9 [120], miR-494 [120], miR-21 [121] and miR-29 [124].…”
Section: Introductionmentioning
confidence: 99%
“…For example, MEG3 is listed in the 32 downregulated core lncRNAs as being downregulated in various types of cancers including breast cancer. Meta-analysis demonstrated that low expression of MEG3 is associated with poor survival in cancer patients [42]. The TN-related lncRNA-mRNA coexpression network derived from the turquoise module displayed MEG3 coexpression pairs.…”
Section: Discussionmentioning
confidence: 99%
“…BioMed Research International in cancer patients [42]. GO analysis of MEG3 linked 219 genes, which enriched cell adhesion, cell proliferation, immune system processes, and other processes.…”
mentioning
confidence: 99%